Improving dosimetric outcome for hippocampus and cochlea sparing whole brain radiotherapy using spot-scanning proton arc therapy. (3rd April 2019) - Ding, Xuanfeng; Zhou, Jun; Li, Xiaoqiang; Blas, Kevin; Liu, Gang; Wang, Yinan; Qin, An; Chinnaiyan, Prakash; Yan, Di; Stevens, Craig; Grills, Inga; Kabolizadeh, Peyman
Summary: This feasibility study shows that Spot-scanning Proton Arc therapy (SPArc) is able to significantly reduce the dose to the hippocampus and cochlea compared to both Volumetric Modulated Arc Photon Therapy (VMAT) and the robust optimized Intensity Modulated Proton Therapy (ro-IMPT) plans in whole brain radiotherapy. Furthermore, SPArc not only improves plan robustness but could potentially deliver a treatment as efficient as ro-IMPT when proton system's energy layer switch time is less than 1 s. Abstract: Purpose: Recently, there have been significant interests towards whole-brain radiotherapy (WBRT) with hippocampal and cochlea sparing. Herein, we present a novel robust, continuous and delivery-efficient spot-scanning proton arc therapy technique (SPArc) to improve such dosimetric outcome. Material and methods : Eight patients were selected for whole brain radiotherapy to evaluate the feasibility of using SPArc for hippocampal and cochlea sparing. Both SPArc and robust optimized Intensity Modulated Proton Therapy(ro-IMPT) plans were generated using the robust optimization of ±3.5% range and 3 mm setup uncertainties and were compared to the Volumetric Modulated Arc Therapy(VMAT). Root-mean-square deviation doses(RMSDs) Volume Histogram, or RVH, was used for proton plan robustness evaluation. Proton plan delivery time was calculated based on a using full gantry rotation with 1 RPM, 2 ms spot switching time, minimum monitor unit per spot = 0.01, and simulate different proton system with energy-layer-switching-time(ELST) from 0.2 to 5 s. Results: SPArc plans showed significant dosimetric improvements in multiple dosimetric parameters. The mean dose to the hippocampus was reduced to 6.20 Gy [RBE] compared to VMAT 10.89 Gy [RBE] ( p < .001) and ro-IMPT 9.38 Gy [RBE] ( p < .001); D100% to the hippocampus was reduced to 4.50 Gy [RBE] compared to VMAT 9.16 Gy [RBE] ( p = .001) and ro-IMPT 7.02 Gy [RBE] ( p = .002); cochlear mean dose was reduced to 7.75 Gy [RBE] compared to VMAT 11.52 Gy [RBE] ( p = .018) and ro-IMPT 10.15 Gy [RBE] ( p = .037); and maximum dose was reduced to 33.84 Gy [RBE] compared to ro-IMPT 36.37 Gy [RBE]. RVH analysis shows SPArc is more robust in Organs-at-risk(OARs) sparing such as hippocampus, cochlea, lens, and eyes. The average total estimated treatment delivery time were 412 s, 627 s, and 1694 s using ELST of 0.2 s, 1 s, and 5 s for SPArc plans, respectively, compared with values of 547 s ( p < .001), 626 s ( p = .484), and 1025 s ( p = .002) for ro-IMPT plans. Conclusion: SPArc could significantly reduce the dose delivered to the hippocampus and cochlea in patients being treated with WBRT. In addition, SPArc plans could potentially achieve similar or faster delivery time in modern proton machine with ELST of less than 1 s.